f-lacunary statistical convergence in topological groups - Sarikaya, Suleyman; Altin, Yavuz (Univ Estadual Maringa, Pro-Reitoria Pesquisa Pos-Graduacao, 2026)
In this study, we will define the concept of f-lacunary statistical convergence in topological groups with the help of an unbounded modulus function. In addition, we will examine some inclusion theorems for different unbounded modulus functions in topological groups.
Keywords: Topological groups; statistical convergence; lacunary statistical convergence